Dictionnaire de la France Médiévale - Franco Júnior, Hilário (Revista de História, 1995)
FAVIER, Jean. Dictionnaire de la France Médiévale. Paris, Fayard, 1993. KIBBLER, Willian & ZINN, Grover (eds.). Medieval France. An Encyclopedia. New York, Garland, 1995.